Diagnostic accuracy of sino-nasal outcome test-22 and lund-kennedy endoscopic score for chronic rhinosinusitis in pre-bone marrow transplantation assessment - Abolfazl Taheri; Arvin Shahzamani; Mahboobe Asadi (Journal of Research in Medical Sciences)
Background: The diagnosis of chronic rhinosinusitis (CRS) is a crucial and challenging entity in bone marrow transplantation candidates. We aimed to evaluate the diagnostic accuracy of the Sino-Nasal Outcome Test (SNOT-22) and Lund-Kennedy endoscopic score for the diagnosis of CRS in bone marrow transplantation candidates. Materials and Methods: We conducted a single-center, observational study evaluating bone marrow transplantation candidates by paranasal sinus computed tomography (CT) scan without contrast to measure the Lund Mackay score. Patients with a Lund Mackay score higher than or equal to four or with any evidence of sino-nasal fungus ball in their paranasal sinus CT were considered CRS. The Lund Kennedy endoscopic score and SNOT-22 were also calculated for all participants. Results: This study included 495 patients, of which 63 were diagnosed with CRS. Participants had a median age of 40 (30, 57) years old and 51.3% were male. The Lund Kennedy score and SNOT-22 were correlated with the Lund Mackay score. Furthermore, both SNOT-22 and Lund Kennedy scores were the predictors of CRS based on univariate logistic regression (odds ratio [95% confidence interval (CI)]: 1.10 [1.06, 1.15], 1.37 [1.22, 1.56], respectively). Lund Kennedy score ≥1 had a sensitivity of 0.78 (95% CI: 0.66, 0.87) and a specificity of 0.76 (95% CI: 0.52, 0.83) (AUC [95% CI]: 0.81 [0.75, 0.87]), while SNOT-22 did not yield a remarkable diagnostic accuracy. Conclusion: The Lund-Kennedy endoscopy score could diagnose CRS in bone marrow transplantation candidates with satisfactory accuracy, whereas SNOT-22 lacks enough accuracy to be employed as an independent sino-nasal assessment modality in these patients.